Development and Validation of an Evaluation Tool for Process Implementation of Foundation Course in Competency-based Medical Education - Anita Chalak; Yogesh Pawade; Shalini Maksane (Archives of Medicine and Health Sciences)
Background and Aim: Competency-based medical education curriculum introduces several innovative reforms like foundation course (FC) in Phase-I MBBS. However, the implementation process of FC has not been evaluated systematically, which necessitates the development and validation of an evaluation tool for FC. This study was aimed to develop and validate a reliable and valid tool for evaluating the implementation process of the FC, in order to enhance its effectiveness. Materials and Methods: This descriptive mixed-method study recruited 33 participants meeting the inclusion criteria. The evaluation tool was developed and shared with six experts participated in Delphi rounds. Multiple Delphi rounds were conducted, the responses were collected, and qualitative feedback from the experts was analyzed. The tool was revised based on the feedback and shared with 16 participants, including the six experts, for evaluating the relevance and usefulness of each item. The content validity ratio (CVR) and content validity index (CVI) of the items were calculated and items were further revised based on these scores. The revised tool was piloted on 17 participants for estimating its reliability. Results: The content validity of the tool was established by statistically high item-CVI (>79%) and scale-CVI (0.946). The CVR values of the items (0.5–1.0) indicated their essentiality. The acceptable reliability of the tool was confirmed by a Cronbach’s α of 0.73. Conclusion: The tool for evaluating the implementation process of FC met the criteria of validity and reliability and can be applied to FC for any medical college in India.